-173-12x=67-2x

Simple and best practice solution for -173-12x=67-2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -173-12x=67-2x equation:


Simplifying
-173 + -12x = 67 + -2x

Solving
-173 + -12x = 67 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
-173 + -12x + 2x = 67 + -2x + 2x

Combine like terms: -12x + 2x = -10x
-173 + -10x = 67 + -2x + 2x

Combine like terms: -2x + 2x = 0
-173 + -10x = 67 + 0
-173 + -10x = 67

Add '173' to each side of the equation.
-173 + 173 + -10x = 67 + 173

Combine like terms: -173 + 173 = 0
0 + -10x = 67 + 173
-10x = 67 + 173

Combine like terms: 67 + 173 = 240
-10x = 240

Divide each side by '-10'.
x = -24

Simplifying
x = -24

See similar equations:

| ×=m•3/m÷4 | | 2x+80=350 | | 12-6-Y=6-4 | | y^2+6y=72 | | 3+Y+2=12-4 | | C/d=2= | | 6+Y=10-Y | | 2x=4(1-x) | | 6x+8=18+5x | | 23=12-(6+x) | | 8x+[5y-(2y-10x)xy]=0 | | 6a(3-a)= | | -6x-133=42-11x | | 9-6x-10=4x+3x-27 | | 4=m•3/m•x | | (0.06)(x)+(0.18)(y)=(0.10)(50) | | x^2=600+-1x | | -6-133=42-11 | | 3x-3(x-1)=3 | | 4-5b+6b^2=0 | | 200+Y+2=252 | | 11-2(3x+2)=4x+15 | | 9-6x+10=4x+3x-27 | | 4x-1=8x-2 | | 18x=90x | | 1.75p-10=0.25p+8 | | x^2+24x-300=0 | | 2p^2/-2p.(-p)^2 | | -158-13x=165+4x | | 19+x/(-2)=9 | | 24=4(u+5)-8u | | 11x-24=45+14x |

Equations solver categories